Pengaruh Perencanaan Pajak dan Asset Perusahaan terhadap Manajemen Laba pada Perusahaan Perdagangan Besar yang terdaftar di Bursa Efek Indonesia Tahun 2012-2015 - Tri Sulistyani; Andika Dwi Kurniawan; Cairin Aulia (Faculty of Economics and Business, University of Pancasakti Tegal, 2016)
The purpose of this study was to determine the effect of tax planning and corporate assets simultaneously and partially on earnings management in large trading companies listed on the Indonesia Stock Exchange in 2012-2015. The population in this study are all companies that are members of large trading companies listed on the Stock Exchange in 2012-2015 with 32 companies. By using a purposive sampling technique obtained 21 companies that meet the criteria as a sample. The data collection method used in this study is documentation. While the data analysis used is testing classical assumptions, multiple linear regression analysis, simultaneous significance test (F statistical test), significant test of individual parameters (statistical test t) and coefficient of determination. Based on the results of the study, the first hypothesis is acceptable, it is proven from the results of testing the significant test simultaneous parameters (F statistical test) obtained probability of a sig value of 0.0012 which is smaller than the value of a which is equal to 0.05. Based on the results of the study, the second hypothesis is acceptable, it is evidenced from the results of testing the significant test of individual parameters (statistical test t) tax planning on earnings management obtained probability of sig value of 0.003 which is smaller than a value of 0.05. Based on the results of the study, the third hypothesis is unacceptable, it is proven from the results of testing the significant individual parameters (statistical test t) company assets to earnings management obtained probability of sig value of, 608 which is greater than a value of 0.05.